Evaluation of municipalities in the Brazilian northeastern according to sustainable development objectives and the triple bottom line - da Silva, Ronaldo Ferreira; Moura, Leonardo de Lima; Gavião, Luiz Octavio; Lima, Gilson Brito; Bidone, Edison Dausacker (Revista Verde de Agroecologia e Desenvolvimento Sustentável, 2017)
The objectives of the sustainable development of the United Nations seek to integrate well-being, poverty reduction and efficient use of natural resources into the notion of economic development. The Triple Bottom Line (TBL) is a parameterized model that proposes the dimensioning of sustainability in the social, economic and environmental dimensions and that can be applied in the evaluation of organizations and municipalities. This article establishes a ranking of fifteen municipalities in the Northeast region for their level of sustainability, using sixteen indicators of actions, activities and public policies aligned with the ODS and from the perspective of the TBL. Each municipality was evaluated in relation to all indicators by the Probabilistic Composition of Preferences (CPP), a multicriteria decision support method. The results demonstrated that the social and economic perspectives involve environmental impacts that can compromise the sustainability of municipalities and that good performance in only one dimension is not enough to express sustainability, reinforcing the importance of sustainable development approach to economic growth.